2019
DOI: 10.1111/jpi.12552
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐7 inhibits melatonin synthesis by acting as a linking molecule between leptin and norepinephrine signaling pathways in pig pineal gland

Abstract: MicroRNAs, including microRNA‐7 (miR‐7), are important modulators of numerous gene expressions and the related biological processes. Melatonin is a key hormone regulating daily and seasonal rhythms, in which a variety of positive and negative regulatory factors, such as norepinephrine (NE) and leptin, are involved. However, the interactions among these factors and the mechanisms remain to be elucidated. The aims of the present study were to identify the functions and the related mechanisms of miR‐7 in regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 68 publications
1
25
0
Order By: Relevance
“…Our results showed that Isl1 deficiency resulted in GT morphological abnormalities and complete absence of the male urethra at E18.5. In support, our results are in agreement with reports that Isl1 is expressed in mesenchymal cells derived from mesoderm, which subsequently forms the prepuce 41,42 .Thus, ISL1 is crucial for several aspects of urethral formation, as in the nervous system 23,24,50 , digestive system 25,26 , and endocrine glands systems 39,40 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results showed that Isl1 deficiency resulted in GT morphological abnormalities and complete absence of the male urethra at E18.5. In support, our results are in agreement with reports that Isl1 is expressed in mesenchymal cells derived from mesoderm, which subsequently forms the prepuce 41,42 .Thus, ISL1 is crucial for several aspects of urethral formation, as in the nervous system 23,24,50 , digestive system 25,26 , and endocrine glands systems 39,40 .…”
Section: Discussionsupporting
confidence: 93%
“…Expression and function of the LIM homeobox protein ISL1 has been extensively studied in the nervous system 23,26,50 , digestive system 24,25 , and endocrine glands 39,40 . Results of the present study demonstrated that Isl1 was expressed in urethral epithelial cells throughout urethral development, and that ablation of Isl1 just prior to GT development in Isl1 MCM/Del mutants led to GT morphological abnormalities and urethral hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 46 differentially expressed miRNAs, 29 were upregulated, and 17 were downregulated (Table S2). Table 1 shows the upregulated miRNAs found in breast (18), oral (3), hepatic (1), gastric (1), colorectal (2), and prostate (2) cancer cell lines. Downregulated miRNAs were found in breast (14), oral (1), and prostate (1) cancer cell lines and in glioma cell lines (1); all miRNAs were validated by RT-PCR.…”
Section: The Meta-analysis Identified 46 Mirnas Differentially Exprmentioning
confidence: 99%
“…15,16 In this context, circadian oscillators and melatonergic signaling molecules can be reciprocally affected by miRNAs. [17][18][19] Although the molecular mechanisms whereby melatonin interacts with miRNAs are only partially known, new information is available regarding its direct or indirect actions on regulatory miRNAs in cancer. 20 In addition to the spread of mutated cells and aberrant expression of miRNAs and their targets in cancer cells, dysregulated miRNAs can be transmitted via exosomes and ectosomes to other cells.…”
Section: Introductionmentioning
confidence: 99%